Studies on shoot and leaf characters of brinjal plants and their quantitative relationships with brinjal shoot and fruit borer - Ahmad, H; Rahman, MH; Haque, MA; Ahmed, KS (Journal of the Bangladesh Agricultural University, 2010)
The field experiment was conducted with twenty brinjal varieties/lines during October 2007 to May 2008 to identify shoot and leaf characteristics of brinjal plants for their susceptibility/resistance against brinjal shoot and fruit borer infestation. Borer infestation was influenced by different characters of plant shoot and leaf. Various parameters like plant height, stem diameter, number of branches and leaves plant-1, third leaf length and width were recorded from different varieties used. The shoot infestation rate was found positively correlated with plant height (0.407), stem diameter (0.520), number of branches plant-1 (0.255), number of leaves plant-1 (0.478), third leaf length (0.373) and third leaf width (0.536). Considering all the recorded parameters, the infestation was found minimum on the variety katabegun WS (1.65%) followed by Marich begun S (1.74%). Keywords: Brinjal shoot and fruit borer; Shoot and leaf characters; Quantitative relationship; Infestation DOI: 10.3329/jbau.v7i1.4794 J. Bangladesh Agril. Univ. 7(1): 29-32, 2009